Development of tablet formulations containing genistein solid dispersion optimized using Box-Behnken design for enhanced solubility - Suranate Phanapithakkun,, Gorawit Yusakul,, Chanakan Sitthisak, Thipapun Plyduang, (Journal of Applied Pharmaceutical Science, 2025)
Genistein, a bioactive isoflavone, offers therapeutic potential but is hindered by poor water solubility, limiting its oral bioavailability. This study aimed to enhance genistein’s solubility by developing solid dispersion (SD) and formulating them into tablets. The SDs were prepared using the solvent evaporation method with polyethylene glycol 4000, poloxamer 407, and crospovidone (XPVP) as carriers. A Box-Behnken design optimized the formulation, yielding a significant increase in solubility to 181.12 μg/ml, closely matching the predicted value. Characterization studies, including differential scanning calorimetry, attenuated total reflectance-Fourier transform infrared spectroscopy, and powder X-ray diffraction, confirmed the conversion of genistein from a crystalline to an amorphous state without interaction with carriers, contributing to improved solubility and dissolution profile. The optimized genistein-SD was further developed into tablets, demonstrating effective drug release. Genistein-SD tablets containing XPVP showed faster disintegration and higher genistein release than those with sodium starch glycolate. Stability testing under long-term and accelerated storage conditions confirmed the retention of genistein content (≥96.61%) over 3 months in both the optimized genistein-SD and genistein-SD tablets. These tablets offer a promising genistein oral delivery approach, supporting further pharmaceutical development.
Keywords: Genistein, solid dispersion, Box-Behnken design, solubility, dissolution